1998
DOI: 10.1111/1467-7660.00093
|View full text |Cite
|
Sign up to set email alerts
|

Circassian Encounters: The Self as Other and the Production of the Homeland in the North Caucasus

Abstract: Diasporas are an increasingly important phenomenon in the ‘era of globalization’. Transnational networks structure and restructure economic exchanges, familial bonds, cultural identities and political mobilization. This article examines one such diaspora, which traces its origin to the North Caucasus, the Circassians. The break‐up of the Soviet Union has enabled some people to journey back to their ‘homeland’ and even take up residence there once again. Through such journeys and the encounters that accompany t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 19 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Although there are other definitions of diaspora, including non-dispersed groups, such as ethnic communities living in adjacent states, and non-victim groups, such as trade diasporas, as a "descriptive typological tool" the definitions of classical and victim diasporas suggested by Cohen and Safran are frequently used to refer to the Adyge and Abkhaz living outside their homeland. Many researchers working on the Adyge and Abkhaz diaspora (also sometimes known as the Circassian or Cherkess diaspora, as explained in note 2) agree with this definition of a classical or victim diaspora (Bram 1999;Kaya 2004Kaya , 2005Shami 1995Shami , 1998Vardania 2007). This article considers that there is variety both within the diaspora and in the ways in which communities conceive their homeland; as a result of their different ideas, various components and members of the diaspora act differently (Pattie 2005, 49).…”
Section: The Adyge-abkhaz Diaspora and Returnmentioning
confidence: 91%
See 1 more Smart Citation
“…Although there are other definitions of diaspora, including non-dispersed groups, such as ethnic communities living in adjacent states, and non-victim groups, such as trade diasporas, as a "descriptive typological tool" the definitions of classical and victim diasporas suggested by Cohen and Safran are frequently used to refer to the Adyge and Abkhaz living outside their homeland. Many researchers working on the Adyge and Abkhaz diaspora (also sometimes known as the Circassian or Cherkess diaspora, as explained in note 2) agree with this definition of a classical or victim diaspora (Bram 1999;Kaya 2004Kaya , 2005Shami 1995Shami , 1998Vardania 2007). This article considers that there is variety both within the diaspora and in the ways in which communities conceive their homeland; as a result of their different ideas, various components and members of the diaspora act differently (Pattie 2005, 49).…”
Section: The Adyge-abkhaz Diaspora and Returnmentioning
confidence: 91%
“…The host countries where the Adyge and Abkhaz resided also became more liberal, giving rise to more cultural freedom. Due to these changes, the last generation of the diaspora grew up in an environment of ethnocultural revival and had a clearer understanding of the political dynamics, territorial divisions, demographic situation, and sociocultural values in the Caucasus (see Doğan 2009;Kaya 2004;Shami 1995Shami , 1998. It was also during these last decades that many people started to visit their homeland; some, with considerate personal effort, return-migrated.…”
Section: The Adyge-abkhaz Diaspora and Returnmentioning
confidence: 99%
“…They are still active in Turkey. They perceive themselves as leftists, although their program has been essentially Circassian-nationalist (Shami 1998). A number of them actually did go back to the Caucasus after 1989; of those, some stayed, while others returned to Turkey in response to cultural, structural, and legal constraints.…”
Section: Minority Politics In the Post-communist Eramentioning
confidence: 99%
“…In the relatively more democratic political and legal context of the 1990s, Circassians established many different associations, most of them mobilized around the idea of an eventual return to the homeland. Many members of the ethnic elite emphasized that their ancestors had been expelled from their homeland and had been tools in the political machinations of the Russian and Ottoman empires; they concluded that a return to the homeland would be inevitable (Shami 1998).…”
Section: Minority Politics In the Post-communist Eramentioning
confidence: 99%
“…6 Appadurai 1996Garnham 1993;Gillwald 1993;Shohat 2003;Sen 2003. space and form for the imagination of communities. 7 Nevertheless, notwithstanding a globalizing world, the state is still important in shaping political realities (Baumann 1996;Duara 1999Duara , 2008Shami 1999). Moreover, the state can be important in defining the shape of cinema.…”
Section: Introductionmentioning
confidence: 99%